Sistem Informasi Mobile untuk Pelacakan Posisi Tikus dan Debu pada Ruangan Storage Museum Lampung - Achmad Musyawir Haikal Fakari; Anisa Ulya Darajat; Sri Purwiyanti; Afri Yudamson (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2023)
The Lampung Museum has the responsibility of serving as a site for the protection and preservation of culturally significant artifacts within the Lampung region ensuring their transfer to future generations Within the museum, there exists a storage room designated for the housing of historical collections Unfortunately, this storage area is frequently neglected, resulting in issues such as damage caused by rodent pests (rats) and the accumulation of dust on the artifacts. In the interest of preventive conservation, this research aims to track the positions of rodents and dust within the storage room and develop an application capable of monitoring the presence of rats and dust.